2017
DOI: 10.1017/s0267190517000125
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic Development During Study Abroad: An Analysis of Spanish Teenagers’ Request Strategies in English Emails

Abstract: Previous research has shown that adolescent second language learners benefit from pragmatic instruction during study abroad (Alcón-Soler, 2015). As a follow-up investigation, the present study looked at late adolescent study-abroad learners, and it examined both the immediate effect of pragmatic instruction and the pragmatic trajectories that adolescent learners follow once they move from the instructional context to real email communication. Email requests in English produced by 60 (30 treatment and 30 contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 36 publications
1
8
0
1
Order By: Relevance
“…The centrality of context-related factors to shed light on developmental patterns, namely teachers' approach to teaching DPMs and the influence of the sociolinguistic context, also supports previous research findings in other learning contexts (Alcón-Soler, 2017;Sánchez-Hernández, 2017;Taguchi, 2011bTaguchi, , 2012, which point out that there is an interaction of factors contributing to shape pragmatic developmental trajectories.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The centrality of context-related factors to shed light on developmental patterns, namely teachers' approach to teaching DPMs and the influence of the sociolinguistic context, also supports previous research findings in other learning contexts (Alcón-Soler, 2017;Sánchez-Hernández, 2017;Taguchi, 2011bTaguchi, , 2012, which point out that there is an interaction of factors contributing to shape pragmatic developmental trajectories.…”
Section: Discussionsupporting
confidence: 82%
“…In an immersion setting, Taguchi (2011bTaguchi ( , 2012 reported quantitative gains in the participants' ability to produce speech acts in English over time, although the qualitative analyses revealed that learners' experiences in the learning context may influence pragmatic change at the individual level. In a study-abroad context, Alcón-Soler (2017) and Sánchez-Hernández (2017) are also examples of how the combination of research methods may reveal patterns of change and the reasons behind individual variation. On the one hand, Alcón-Soler (2017) analysed the effect of instruction of email requests and the reasons behind the patterns of change observed, reporting that, although the frequency of request mitigators increased after the instructional treatment, learners' perception of the study-abroad experience interacted with instructional effects and influenced request production over time.…”
Section: Pragmatics In Multilingual Written Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings from this review show that many studies have been conducted to identify the instructional effects on L2 requests over the past decades although the bulk of research concentrated on oral L2 requests. In contrast, only very few studies assessed the teachability of L2 email requests (Alcón-Soler, 2015, 2017; Chen, 2015; Ford, 2006; Nguyen, 2018; Nguyen et al, 2015, 2019). Ford (2006) was among the first to assess the instructional effects on composing requestive emails.…”
Section: Literature Reviewmentioning
confidence: 99%